Estudo de comportamento mecânico de uma cortina de estacas atirantada - Pedro Santana Moreira (2016)
The contiguous piled wall with ground anchor are elements widely used in the construction of residential buildings, industrial buildings and mining, mainly due to the local topography and the construction of underground floors. In relation to conventional solutions, such as conventional anchored wall and diaphragm wall, the contiguous pile wall with ground anchor stands out for its low cost and deadline. This work aimed at the retroanalysis of the mechanical behavior of a sector of a retaining built with piled with ground anchor by numerical modeling. The soil resistance parameters were evaluated and, using the finite element method, in a 2D and 3D stress strain analysis, a retroanalysis was performed based on the results obtained in the inclinometer instrumentation. So, the shear strength parameters were tested within a range established by a statistical analysis made with the results of the laboratory tests (triaxial shear test) and field tests (CPTu, DMT, PMT and SPT) performed for the project. In the initial phase of 2D numerical analysis, the upper and lower limits were studied, as well as the average of the results of the parameters obtained in the tests. It was possible to verify which values of resistance and compressibility parameters led the model to better represent the measured horizontal displacements, indicating if the tests reach parameters capable of reproducing the horizontal displacements measured by the inclinometers. The efforts of the retaining (earth pressure, moment and shear force) in 2D and 3D modeling were compared. Some divergences between models were found, the horizontal displacements of the retaining in the 3D condition, using the same parameters of the 2D analysis, were smaller. Therefore, the earth pressure was greater in the 3D analysis, allowing smaller displacements. It was possible to identify the difference of 66% in shear stress when comparing the results of numerical analysis 2D and 3D. Regarding the moment, this difference was 30%.